The invasive mosquito Aedes japonicus japonicus is spreading in northeastern Italy - Montarsi, Fabrizio (Parasit Vectors, 2019)
BACKGROUND: The invasive mosquito species, Aedes japonicus japonicus, was detected in northeastern Italy for the first time in 2015, at the border with Austria. After this finding, a more intensive monitoring was carried out to assess its distribution and to collect biological data. Herein, we report the results of four years (2015–2018) of activity. METHODS: The presence of Ae. j. japonicus was checked in all possible breeding sites through collections of larvae. The monitoring started from the site of the first detection at the Austrian border and then was extended in all directions. The mosquitoes were identified morphologically and molecularly. RESULTS: Aedes j. japonicus was found in 58 out of 73 municipalities monitored (79.5%). In total (2015–2018), 238 sampling sites were monitored and 90 were positive for presence of Ae. j. japonicus larvae (37.8%). The mosquito was collected mainly in artificial containers located in small villages and in rural areas. Cohabitation with other mosquito species was observed in 55.6% of the samplings. CONCLUSIONS: Aedes j. japonicus is well established in Italy and in only four years has colonised two Italian Regions, displaying rapid spreading throughout hilly and mountainous areas. Colonization towards the south seems limited by climatic conditions and the occurrence of a large population of the larval competitor, Ae. albopictus. The further spread of Ae. j. japonicus has the potential to pose new threats of zoonotic agents (i.e. Dirofilaria spp. and West Nile virus) within areas at altitudes previously considered at negligible risk in Italy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-019-3387-x) contains supplementary material, which is available to authorized users.